Advances in applied microbiology. - Laskin, Allen I., 1928-; Sariaslani, Sima; Gadd, Geoffrey M. (Academic Press/Elsevier, 2011)
Published since 1959, Advances in Applied Microbiology continues to be one of the most widely read and authoritative review sources in microbiology. The series contains comprehensive reviews of the most current research in applied microbiology. Recent areas covered include bacterial diversity in the human gut, protozoan grazing of freshwater biofilms, metals in yeast fermentation processes and the interpretation of host-pathogen dialogue through microarrays. Eclectic volumes are supplemented by thematic volumes on various topics, including Archaea and sick building syndrome. Impact factor for 2009: 1.860. * Contributions from leading authorities and industry experts * Informs and updates on all the latest developments in the field * Reference and guide for scientists and specialists involved in advancements in applied microbiology.